Myth analyzed - Segal, Robert Alan 1948-2024 (Theorists of myth, 2021)
"Compiling and critiquing modern theories and theorists of myth, this book offers an overview of theories around the origin and function of various mythologies and mythological figures, allowing wider theoretical claims to be made about the relationship between societies and their myths. This ambitious collection of essays uses the tools and viewpoints of a range of disciplines in order to advocate for theoretical generalizations about myth as a whole. The book is divided into five sections, covering topics such as, myth and psychoanalysis; hero myths; myth and science; myth and politics; and myth and the physical world. Chapters engage with Freud, Jung, Popper and other thinkers, demonstrating how myth still plays a vital role in our communities and individual identities. The synthesising of these theories allows the reader to see that myths tend to be the result of a need, either material or existential, rather than a spontaneous creation. This is a fascinating survey by a leading voice in the study of myth. As such, it will be of great interest to scholars of myth and how it interacts with Sociology, Anthropology, Politics and Economics"--